An Exploratory Pilot Study to Describe Shared Decision-Making for PTSD Treatment Planning: The Provider Perspective. (21st March 2019) - Etingen, Bella; Hill, Jennifer N; Miller, Laura J; Schwartz, Alan; LaVela, Sherri L; Jordan, Neil
Abstract: Objective: To describe current practices used by Veterans Administration (VA) mental health (MH) providers involved in post-traumatic stress disorder (PTSD) treatment planning to support engagement of veterans with PTSD in shared decision-making (SDM). Methods: Semi-structured interviews with MH providers ( n = 9) were conducted at 1 large VA, audio-recorded, and transcribed verbatim. Transcripts were analyzed deductively, guided by a published account of the integral SDM components for MH care. Results: While discussing forming a cohesive team with patients, providers noted the importance of establishing rapport and assessing treatment readiness. Providers' clinical knowledge/expertise, knowledge of the facility's treatment options, knowledge of how to navigate the VA MH care system, and patient factors (goals/preferences, factors influencing treatment engagement) were noted as important to consider when patients and providers exchange information . When negotiating the treatment plan, providers indicated that conversations should include treatment recommendations and concurrent opportunities for personalization. They also emphasized the importance of discussions to finalize a mutually agreeable patient- and provider-informed treatment plan and measure treatment impact. Conclusion: These results offer a preliminary understanding of VA MH providers' facilitation of SDM for PTSD care. Findings may provide insights for MH providers who wish to engage patients with PTSD in SDM.